Inspiration from New Discoveries in Vascular Endothelial Cell Growth: A Bold Conjecture about Mature Cell Growth - Jingan Li; Yachen Hou; Kun Zhang (Current Approaches in Science and Technology Research Vol. 4, 2021)
For vascular biomaterials and devices, how to accelerate the growth of endothelial cells (EC), so as to achieve the repair, regeneration or construction of endothelial monolayer as soon as possible is the goal pursued by scientists for decades. A variety of techniques have been developed to achieve this goal by directly promoting EC growth on the surface and inhibiting smooth muscle cells (SMC) and macrophages. However, a new discovery from 2017 that endothelial monolayer in the regenerated tissues doesn’t contact with the implanted biomaterials provide us novel inspiration, and proposed the concept of “spatiotemporal orderliness of function” to declare the behaviors of macrophages, SMC and EC on the implanted biomaterials in time sequence and space sequence, and the functions endowed for the implants’ surfaces should follow this objective phenomenon and law. To our surprise, we found a series of new secrets of EC growth in the subsequent research. These details, which are so insignificant and even neglected in scientific research, are not limited to explaining the reasons for various blood implantation failures, but may reveal some new rules different from the previous cognition for the universal mature cell growth.